2009
DOI: 10.1002/ptr.2641
|View full text |Cite
|
Sign up to set email alerts
|

1‐methyl malate from Berberis integerrima fruits enhances the antibacterial activity of ampicillin against Staphylococcus aureus

Abstract: The enhancement of the antibacterial activity of ampicillin by different extracts of Berberis integerrima fruits was evaluated against Staphylococcus aureus. Disk diffusion and agar dilution methods were used to determine the antibacterial activity of ampicillin in the absence and presence of different plant extracts or various fractions eluted by column chromatography. A clinical isolate of S. aureus was used as a test strain. The active component of B. integerrima fruits involved in the enhancement of ampici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The essential oil of Cinnamon zirconium has been reported to enhance the activity of clindamycin against toxicogenic Clostridium difficile [11]. We have also recently reported that the ethanol extract of Berberis integerrima and its active component (1-methyl malate) can increase the antibacterial activity of ampicillin against the clinical isolates of Staphylococcus aureus [13]. The ethanol extract of S. saligna showed antifungal activity against the test strains used (except A. flavus).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The essential oil of Cinnamon zirconium has been reported to enhance the activity of clindamycin against toxicogenic Clostridium difficile [11]. We have also recently reported that the ethanol extract of Berberis integerrima and its active component (1-methyl malate) can increase the antibacterial activity of ampicillin against the clinical isolates of Staphylococcus aureus [13]. The ethanol extract of S. saligna showed antifungal activity against the test strains used (except A. flavus).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, various natural products or synthetic compounds have been reported to increase the antibacterial activity of the presently used antibiotics against different clinical isolated resistant test strains [5][6][7][8][9][10][11][12][13]. The essential oil of Cinnamon zirconium has been reported to enhance the activity of clindamycin against toxicogenic Clostridium difficile [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. integrima produced no effect on the alpha glucosidase and the pancreatic lipase activity (1417). 1-methylmalate, one of the B. integrima fruit components, increased the anti-microbial activity against Staphylococcus aureus (18). Isoquinoline alkaloids attained from the root of Turkish berberis species showed an anti-inflamatory and anti-nociceptive effects (19), whereas in our study this plant exhibited the anti-cholinesterase activity.…”
Section: Discussionmentioning
confidence: 99%
“…The plant grows in different parts of the world and has a long history in traditional medicine (6). Some of its alkaloids, such as berberine, berbamine, palmatine, oxyacanthine, condocorine, tetrandrine, have been identified after degradation, with different healing properties (7,8). Souri et al (9) studied the antioxidant properties of 60 plant species native to Iran and showed that barberry has high antioxidant properties (49.95% in 0.4 micrograms).…”
Section: Introductionmentioning
confidence: 99%